Control of Salvinia molesta with imazamox and analysis of environmental indicators in microcosms - Garlich, Nathalia [UNESP]; Garcia, Guilherme Leonardi; dos Santos, Karina Petri; de Oliveira, Ana Carolina; Pitelli, Robinson Antonio; da Costa Ferreira, Marcelo [UNESP]; da Cruz, Claudinei (Taylor & Francis, 2021)
The aim of this study was to assess the efficacy of imazamox for control of S. molesta and to assess the effects of plant decomposition on environmental indicators after application of this herbicide in microcosm conditions. The following rates were used: 600, 700, 800 and 900 g ai ha−1 and spray volume 50 L ha−1. Control efficacy was determined as the percentage (from 0 to 100%) of visible injury symptoms in the plants, biochemical and chemical oxygen demand (BOD5 and COD), water quality variables, chlorophyll a and pheophytin a at 0, 7, 15, 30, 45 and 60 days after application (DAA) and fresh and dry biomass at 60 DAA. Imazamox was effective in controlling 94% of S. molesta with 900 g ai ha−1; it reduced 95% of fresh weight and 92% of dry weight of plant at 60 DAA, and reduced chlorophyll a of the plants for all rates. For BOD5, there was an increase for all rates at 15, 30 and 45 DAA with restoration of the parameters at 60 DAA, and for COD, there was an increase at 60 DAA with 700 and 900 g ai ha−1. For temperature, pH, dissolved oxygen and electrical conductivity, there was no significant effect after spraying. Imazamox was effective in controlling S. molesta with 900 g ai ha−1 without causing significant effects on the physical-chemical parameters of water quality.
Keywords: Aquatic environment; chemical control; environmental monitoring; herbicide; Salvinia molesta; water quality